1988
DOI: 10.1111/j.1559-1816.1988.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Interview Strategies For People with a Visible Disability1

Abstract: A total of 117 students participated in the present investigation, which compared wheelchair-user and able-bodied job applicants as well as two interview-taking strategies available to wheelchair users: disclosing the disability during the telephone screening or not doing so and acknowledging it only during a face-to-face interview. Results show that wheelchair-user applicants were evaluated more favorably than able-bodied applicants during the telephone interview, a finding consistent with the positivity bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
(18 reference statements)
2
25
0
Order By: Relevance
“…Students may be reluctant to disclose their disability for fear of negative social stigma. Some research suggests that job applicants are viewed more favorably if they do not disclose their disabilities until a face-to-face interview (e.g., Tagalakis, Amsel, & Fichten 1988). For students with invisible disabilities, such as a learning disability, the issue of disclosure can become more complex because they have the option of never disclosing their disability.…”
Section: Scope Of Vocational Guidancementioning
confidence: 99%
“…Students may be reluctant to disclose their disability for fear of negative social stigma. Some research suggests that job applicants are viewed more favorably if they do not disclose their disabilities until a face-to-face interview (e.g., Tagalakis, Amsel, & Fichten 1988). For students with invisible disabilities, such as a learning disability, the issue of disclosure can become more complex because they have the option of never disclosing their disability.…”
Section: Scope Of Vocational Guidancementioning
confidence: 99%
“…For these and other reasons, people with disabilities follow different work trajectories than non-disabled persons. People with a chronic disease or disability have more trouble in finding employment that fits their interests and competencies than healthy people ([van Lindert et al, 2006] and [Tagalakis et al, 1988]).…”
Section: Introductionmentioning
confidence: 99%
“…These stereotypes consisted of both the positive traits of being quiet, honest, softhearted, nonegotistical, and undemanding, and the negative traits of being nervous, unaggressive, insecure, dependent, and unhappy (Fichten & Amsel, 1986;Fichten, et al, 1989). Still other researchers have found that students without disabilities rated students with disabilities positively (e.g., Belgrave, 1985;Belgrave & Mills, 1981;Tagalakis, Amsel, & Fichten 1988;Weinberg-Asher, 1976). Fichten et al (1989) reconciled the disparate findings by suggesting that "the prevalence of positive descriptions of individuals with disabilities may be due to social desirability, sympathy, or self-presentation biases" (p. 244) on the part of individuals who are not disabled.…”
mentioning
confidence: 98%